(untitled) (Scientific journal of the Fergana State University, 2023)
Physicochemical properties of nitrogen and sulfur-containing aluminosilicates were studied by amine ionization of vermiculite in the presence of polyethylene polyamine. To do this, modifications were made in the same amount, at different times, temperatures, and at different concentrations. The resulting ionite was titrated with alkali and the SЕS value was determined.